Implementasi Undang-Undang RI Nomor 22 Tahun 2009 Tentang Lalu Lintas dan Angkutan Jalan (Studi di Kota Ambon) - Fauzia Rahawarin (TAHKIM, 2017)
This study on the application of traffic laws aimed to determine the implementation of Law No. 22 of 2009 on traffic and road transport as well as the view of sociology of law on the level of compliance, adherence and awareness in the city of Ambon in motorcycle riding. Data were collected through field research and descriptive analysis qualitative. The results showed that the implementation of Law No. 22 Year 2009 regarding Traffic and Road Transportation already applied in the middle of Ambon City community. Unit Resort Police Ambon and PP. Lease disseminate legislation traffic and road transport in all kinds of places such as in schools of the first level or primary school, junior high, and high schools, bases taxis, offices, and campus. But in sociology of law on the level of compliance, adherence and awareness in the city of Ambon in riding motorcycles in traffic is low. Because, still common violations in road traffic, such as pengedara motorcycles were not wearing helmets and carrying no driver's license, vehicle registration, vehicle accessories and do not turn on the lights during the day. Thus the implementation of the Act have not been able to increase compliance and public awareness of the cultural city of Ambon orderly traffic. Keywords: implementation, traffic laws, motorcyclists, violations